COMBINED TECHNIQUES OF CAUDAL EPIDURAL BLOCK AND TRANSFORAMINAL NERVE ROOT BLOCK IN THE TREATMENT OF DEGENERATIVE DISEASES OF THE LUMBAR SPINE: A COST-EFFECTIVENESS ANALYSIS - Marília de Jesus Nogueira; Anderson Gomes Marin; Mariana Demétrio de Sousa Pontes; Carlos Fernando Pereira da Silva Herrero (Acta Ortopédica Brasileira)
ABSTRACT Objective: This study aims to assess cost-effectiveness of caudal epidural block with transforaminal nerve root block in the treatment of degenerative diseases of the lumbar spine. Methods: A total of 47 patients with lumbar sciatica symptoms were included. Low back pain and leg pain were assessed using the visual analogue scale (VAS), both in the pre-procedure and one week after. The cost-effectiveness and value required to improve each point on the VAS were estimated using addition, division, and rule of three calculations. Results: For low back pain, scores ranging from 2 to 10 were found before the procedure, with a mean of 7.5 ± 2.14 (95%CI: 6.8–8.1). A week after, these scores ranged from 0 to 10, with a mean of 3.1±2.8 (95%CI: 2.3–4.0; p < 0.0001). Regarding leg pain, scores ranging from 1 to 10 were noted before the procedure, with a mean of 6.8 ± 2.5 (95%CI: 6.1–7.4). A week after, these scores ranged from 0 to 9, with mean of 2.4 ± 2.5 (95%CI: 1.8–3.1; p < 0.0001). The cost of the materials used during the procedure was 214.72 BRL. Conclusion: Caudal epidural with transforaminal nerve root block were a cost-effective treatment modality for patients with degenerative diseases of the lumbar spine. Level of evidence III, Retrospective cohort study.